Investigation of Housekeeping Principles and Its Effective Factors in Micro-Scale Enterprises in 2015, Shiraz, Iran. - Anahita FAKHERPOUR; Mehdi JAHANGIRI; Sepideh MONSEF; Mohadeseh NEZAM (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Micro-scale enterprises play a vital role in development of national economics and self-employment. However, these industries due to lack of proper safety controls including poor housekeeping, َas well as low awarenessabout safety behaviors and procedures, do not have  adequate healthand safety condition. This study was aimed to assess housekeeping principles and its effective factors in Shiraz micro-scale enterprises. Methods: This cross-sectional study was conducted on 300 selected micro-scale enterprises in Shiraz. A researcher-made checklist with reliability and validity of 0.851 was used for the study. Results: The mean score of housekeeping among studied enterprises was calculated to be 58.69 11.23%., The maximum and minimum scores among different housekeeping fields were related to equipment layout, and labeling calculated about 8.99±39.06%, and 5.77±3.77%, respectively. Among studied variables, there was a significant relationship between the type of activity and the incident report with housekeeping score (p<0.05). Conclusion: This study showed the rate of incident report was higher among enterprises having better housekeeping status which could help enterprises in better safety management including planning for prevention and reduction of incidents.